Did the Presidency of Lyndon B. Johnson and the Appointment of Thomas C. Mann as Assistant Secretary of State for Inter-American Affairs Mark an End to the Idealistic Approach towards Latin America of John F. Kennedy's Alliance for Progress? - Tunstall Allcock, Thomas (2008)
This dissertation will be assessing the Latin American record of President Lyndon Baines Johnson. Emphasising the lack of detailed historical research on this subject, it will be demonstrated that current interpretations of his achievements are relatively simplistic and overly critical. Particular attention will be given to the Alliance for Progress, a program created by John F. Kennedy, Johnson's predecessor, designed to modernise various aspects of Latin American society. Central to current perceptions of Kennedy and Johnson's relative performances in Latin American affairs are the views expressed by former Kennedy associates, who have argued that Johnson destroyed a noble and potentially successful cause by abandoning the idealistic aspects of the Alliance in favour of economic and geo-political practicalities. This interpretation will be challenged by demonstrating that under Johnson the Alliance was actually more successful, and that Kennedy's commitment to the more morally appealing aspects of the program has been exaggerated. It will also be demonstrated that evaluations of Johnson's Latin American record have been coloured by his performance in other regions, as well as by unfair comparisons with his predecessor. Thomas C. Mann, Coordinator for the Alliance under Johnson, will also be given particular attention as criticisms of his performance have often been fundamental to assessments of Johnson's Latin American policy. It will be shown that both men achieved more than they are commonly credited with and are deserving of reappraisal.